The Effect of Garlic (Allium sativum) Extract Pesticides in Repelling Rice Eating Bird Pests - Hardiansyah, Muhammad Yusril; Al Ridho, Arif Fikri; Nurhidayat (Indonesian Journal of Agricultural Research, 2020)
One of the main problems in rice cultivation is the difficulty of controlling bondol bird (Lonchura punctulata) pest attacks. Bird pest is one of the main enemies of farmers that can reduce crop production. Increasing bird populations cause crop yields to decline. So that one way that can be used in repelling bird pests is by giving pesticides from garlic extract. Allicin is a compound that gives garlic its distinctive smell which repels bird pests. This study aims to determine the effect of the provision of plant-based pesticides from garlic extract in repelling rice-eating bird pests. This research was conducted in Tonasa Village, Takalar District, South Sulawesi, Indonesia. Research implementation methods include the manufacture and testing of pesticides liquid extracts of garlic and application in the field by spraying, this spraying is carried out in the morning, afternoon, and evening before making the observations. Observation parameters use the method of comparing initial observations and final observations observed in the morning, afternoon and evening (comparison method) by conducting initial data collection (without using pesticides) and final data collection (after spraying pesticides), the average number of groups of birds that attack 1 Ha of rice fields. The results obtained on average indicate quite a lot of attacks in a day, especially in the morning. After the use of the automatic repellent method the attacks of bondol bird groups tend to decrease where in the morning ratio of 20 to 33 decreases to 5 to 13 attacks, while the ratio of daytime 8 to 15 decreases to 3 to 7 attacks and the ratio of the evening 19 to 33 decreases to 6 to 12 bird group attacks. So that the administration of garlic extract pesticides is effective in reducing bird pest attacks.